Physiological and Biochemical Responses to Aluminum Stress in the Root of a Biodiesel Plant Jatropha curcas L. - RADITE TISTAMA; UTUT WIDYASTUTI; DIDY SOPANDIE; AKIHO YOKOTA; KINYA AKASHI; . SUHARSONO (Bogor Agricultural University, Indonesia, 2012)
We investigated J. curcas responses to aluminum stress, histochemically and biochemically. Histochemical stainings were observed to analysis aluminum accumulation, lipid peroxidation and the loss of plasma membrane integrity on the surface and tissue of the root apex. Enzymatic analysis was conducted to measure malate content in leaf, root and malate efflux in the medium. We used M. malabathricum as a comparison for Al-tolerance plant. J. curcas root elongation was inhibited by 0.4 mM AlCl3, while M. malabathricum root elongation was inhibited by 0.8 mM AlCl3 treatment. Inhibition of root elongation has high correlation with Al accumulation in the root apex, which caused lipid degradation and cell death. Generally, malate content in J. curcas leaf and root was higher than that in M. malabathricum. In the contrary malate efflux from the root into the medium was lower. J. curcas root has a different pattern compared to M. malabathricum in malate synthesis and malate secretion when treated with a different Al concentration. We categorized J. curcas acc IP3 as more sensitive to aluminum than M. malabathricum.